Restriction of plasmid DNA during transformation but not conjugation in Neisseria gonorrhoeae. - Stein, D C (1988)
Neisseria gonorrhoeae strains WR302 and PGH3-2 were characterized with respect to their restriction-modification phenotype. WR302 DNA was cleaved by HaeIII, indicating the lack of methylation at the GGCC sequence. PGH3-2 produced NgoSI (an isoschizomer of NgoII). WR302 produced a restriction enzyme with a recognition sequence different from that of NgoI, NgoII, or NgoIII. Plasmid pFT180 isolated from WR302 was unable to transform PGH3-2, whereas plasmid pFT180 isolated from PGH3-2 was able to transform PGH3-2 at a very high frequency. When plasmid pFT180 isolated from WR302 was methylated in vitro with meth M. HaeIII, this plasmid was able to transform PGH3-2. NgoSI was able to restrict WR302 DNA in vitro, whereas it was incapable of restricting PGH3-2 DNA in vitro. When the self-transmissible R factor pFT6 was mobilized from WR302 to PGH3-2 by conjugation, a 1-order-of-magnitude difference in transfer frequencies was observed, as compared with an isogenic cross. The data indicate that host-mediated restriction can prevent the gonococcus from acquiring DNA via transformation but not via conjugation.